2021
DOI: 10.3892/etm.2021.9855
|View full text |Cite
|
Sign up to set email alerts
|

Laminar shear stress upregulates the expression of PPARs in vascular endothelial cells under high free fatty acid‑induced stress

Abstract: Shear stress has been reported to result in various metabolic effects in endothelial cells (ECs), which in turn contribute to the regulation of their vascular functions. Peroxisome proliferator-activated receptors (PPARs) have been reported to regulate lipid metabolism and have been implicated in metabolic disorders. The present study assessed the effects of laminar shear stress on the expression of PPARs in ECs in the presence of high concentrations of free fatty acids (FFAs). Human aortic ECs (HAECs) were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…PPARs belong to the nuclear receptor superfamily of ligandactivated transcription factors regulating lipid and glucose metabolism, energy homeostasis, and inflammation (73). Previous studies have demonstrated that shear stress induces PPARα, PPARδ, and PPARγ to regulate endothelial function (74,75). PPARγ agonists belong to the thiazolidinedione class of drugs such as troglitazone and rosiglitazone that attenuate palmitate-induced ER stress and apoptosis by activating SCD1 induction in macrophages (76).…”
Section: Discussionmentioning
confidence: 99%
“…PPARs belong to the nuclear receptor superfamily of ligandactivated transcription factors regulating lipid and glucose metabolism, energy homeostasis, and inflammation (73). Previous studies have demonstrated that shear stress induces PPARα, PPARδ, and PPARγ to regulate endothelial function (74,75). PPARγ agonists belong to the thiazolidinedione class of drugs such as troglitazone and rosiglitazone that attenuate palmitate-induced ER stress and apoptosis by activating SCD1 induction in macrophages (76).…”
Section: Discussionmentioning
confidence: 99%
“…Shear stress during laminar flow increases the expression of LXRs in endothelial cells through the PPARγ pathway, which is induced by laminar flow [ 290 , 291 ]. It was shown that the expression of LXRa, LXRβ and their target genes is higher in the endothelium of the mouse thoracic aorta, where laminar blood flow is assumed, than in areas with impaired flow, for example, in the aortic arch region [ 292 ].…”
Section: The Intersection Of Endothelial Biomechanical Properties and Protein Functionmentioning
confidence: 99%
“…In an in vivo setting, endothelial cells (EC) encounter blood flow-mediated shear stress of variable intensity and pattern, which has profound effects on multiple EC functions including gene expression and metabolism [21][22][23][24][25][26][27]. Laminar pulsatile shear stress generated in straight vascular regions is protective for the endothelium, whereas turbulent/oscillatory shear stress in branches of the conduit arteries is associated with atherogenesis [21,23,26,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Laminar pulsatile shear stress generated in straight vascular regions is protective for the endothelium, whereas turbulent/oscillatory shear stress in branches of the conduit arteries is associated with atherogenesis [21,23,26,28,29]. In particular, laminar shear stress confers protection against FFA lipotoxicity via decreased ROS generation, downregulation of inflammatory cascades, and antiapoptotic action [27,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%